Analisis Dampak Digitalisasi UMKM terhadap Pertumbuhan Ekonomi Lokal di Indonesia - mutiarani; Gustina Masitoh; novi royani; Dewi Mitasari; Thamara idil fitri (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze the impact of digitalization on regional economic growth through strengthening Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The approach used is a systematic literature review that examines how digitalization can expand market reach, improve operational effectiveness, and encourage innovation among MSMEs. The findings show that digitalization plays an important role in increasing local productivity and competitiveness of MSMEs, thus contributing to the acceleration of economic growth at the local level. However, there are still obstacles such as inequality in digital infrastructure, low technological literacy, and suboptimal regulations that hinder the maximum utilization of digitalization. The findings of this study provide recommendations to policy makers and MSME players in order to strengthen the digital ecosystem to support inclusive and sustainable economic growth in Indonesia.